2017
DOI: 10.2147/ott.s95267
|View full text |Cite
|
Sign up to set email alerts
|

PI3K/AKT/mTOR pathway promotes progestin resistance in endometrial cancer cells by inhibition of autophagy

Abstract: Endometrial cancer (EC) is now one of the most common malignant tumors in young women. In all, 90% of young patients with EC have a high expression of progesterone recep tor, can be treated with progestin, and have very good prognosis. However, some of the young EC patients are resistant to progestin, the mechanism of which is unclear. To illuminate the mechanism by which endometrial cells acquire progestin resistance, we treated Ishikawa cells by slowly increasing dosage of progestin and established a progest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 24 publications
3
48
0
Order By: Relevance
“…In type I endometrial cancer, as autophagy is repressed by activated PI3K/AKT/mTOR signaling pathway, the proliferation of tumor cells becomes facilitated, indicating that autophagy inhibits the development of tumors. Hua Liu, et al showed that activation of the PI3K/AKT pathway could result in activation of mTOR and the proliferation of endometrial cells by inhibiting autophagy [18]. Currently, autophagy is considered as a "double-edged sword", since it not only inhibits tumor progression by depriving cells of nutrients and energy, but also promotes tumor progression by conferring cells with nutrients and energy [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…In type I endometrial cancer, as autophagy is repressed by activated PI3K/AKT/mTOR signaling pathway, the proliferation of tumor cells becomes facilitated, indicating that autophagy inhibits the development of tumors. Hua Liu, et al showed that activation of the PI3K/AKT pathway could result in activation of mTOR and the proliferation of endometrial cells by inhibiting autophagy [18]. Currently, autophagy is considered as a "double-edged sword", since it not only inhibits tumor progression by depriving cells of nutrients and energy, but also promotes tumor progression by conferring cells with nutrients and energy [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…Aberrant PI3K/AKT signalling has been described in many human cancers, including soft tissue sarcomas [51][52][53][54][55][56][57], and AKT activation contributes to pathways that promote tumour cell proliferation, invasion and metastasis [58,59]. Indeed, there is compelling evidence that a key requirement for the development of RMS is the prolonged activation of serine/threonine kinases such as AKT [60].…”
Section: Introductionmentioning
confidence: 99%
“…With an increasing number of women electing to delay childbearing, there is a critical need for adequate treatment without hysterectomy for nulliparous women with EC (3). Progestins, are widely used in young early EC patients as conservative endocrine treatment (4). Progesterone, a tumor suppressor in the endometrium, plays a critical role in cell differentiation, cycle, and apoptosis (5).…”
Section: Introductionmentioning
confidence: 99%
“…Progesterone, a tumor suppressor in the endometrium, plays a critical role in cell differentiation, cycle, and apoptosis (5). Approximately 90% of young patients can be treated with progestin due to a high expression of progesterone receptor (PR), which often results in a good prognosis (4). A meta-analysis indicates that 72 percent of patients achieved remission by oral progesterone, and the pregnancy outcome is about 35-40% (6,7).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation